Marketing Practices in Australian Libraries: Is Promotion Enough?. Issue 2 (3rd April 2018) - Velasquez, Diane L.; Campbell-Meier, Jennifer
Abstract: Marketing is necessary for all organisations working with a changing client or user base. In order to gauge current marketing practices in libraries, a survey and focus groups were conducted with 36 workshop participants primarily from libraries in Australia. The participants were from a wide range of library backgrounds and it was evident that the focus groups identified a wide range of practices. Participants discussed current marketing activities, highlighting some of the unique ways that libraries are marketing services and collections. Not all libraries have the support and budget necessary to develop a marketing campaign, but librarians can adopt best practices and identify strategies that increase awareness. Libraries may accomplish this by using social media, developing outcomes based marketing plans and being prepared with elevator speeches or stories to explain the library's role within the community. These tactics are deemed necessary as libraries are competing with the Internet to fill the information needs of community members. They are also competing with business, social and educational activities, trying to draw individuals to programmes and services offered. After discussing the current marketing activities participants identified, this paper makes recommendations from the literature about ways of making marketing more efficient in the future.